The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1115/1.2833874
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Experimental Data for Fixed Geometry Hydrodynamic Journal Bearings

Abstract: An extensive survey of the experimental research on the static and/or dynamic characteristics of fixed geometry, hydrodynamic journal bearings, available in English, in the open literature is presented. The type(s) of bearing, size of bearing(s) and range of parameters measured in each work are reported for slightly over 100 published experimental works. In addition, some general observations about the available experimental data sets are made. This annotated survey is intended to help the analytical community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…He found that the typical agreement of the various experimental methods with theoretical values was within 20 percent, though some cases of discrepancies of 100 percent or more had been reported by some authors. Swanson and Kirk provided a literature review of fixedgeometry bearing tests in tabular format [23].…”
Section: Previous Literature Reviewsmentioning
confidence: 99%
“…He found that the typical agreement of the various experimental methods with theoretical values was within 20 percent, though some cases of discrepancies of 100 percent or more had been reported by some authors. Swanson and Kirk provided a literature review of fixedgeometry bearing tests in tabular format [23].…”
Section: Previous Literature Reviewsmentioning
confidence: 99%
“…Childs (1993) gave a comprehensive survey of the rotordynamic experimental data for liquid and gas annular seals and turbines and pump impellers along with their geometry and operating conditions. Swanson and Kirk (1997) presented a survey in tabular form of the experimental data available in the open literature for fixed geometry hydrodynamic journal bearings. They categorized the literature based on bearing type, bore diameter, length to diameter ratio and type of data available (i.e.…”
Section: Referencesmentioning
confidence: 99%
“…He found that the typical agreement of the various experimental methods with theoretical values was within 20 percent, though some cases of discrepancies of 100 percent or more had been reported by some authors. Swanson and Kirk provided a literature review of fixed-geometry bearing tests in tabular format [25].…”
Section: Previous Literature Reviewsmentioning
confidence: 99%